The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1002/poc.3779
|View full text |Cite
|
Sign up to set email alerts
|

Hunting for smectic C in calamitic azobenzene ionic liquid crystals with different cationic head groups

Abstract: b b br r r r r r r r r r r r r r ra a a a a a a a a a a a a a ar r r r r r r r r r r r r r ry y y y y y y y y y y y y y y.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 58 publications
(62 reference statements)
0
17
0
Order By: Relevance
“…[12][13][14][15][16] We have previously identied ILCs 1, 2 showing rare SmC phases (Scheme 1), which consist of a calamitic core unit carrying one side chain and a exible spacer connected to a cationic head group. [15][16][17][18] Upon examination of the order parameter of the SmA phase of these compounds it was found that the long range orientational order (S 2 ) in the SmA phase was much smaller as compared to the values obtained for SmA phases from non-ionic liquid crystals. [19][20][21][22] On the other hand, the 1D translational order (smectic order parameter 3) of the SmA phase of ILCs is much larger 17,18 as compared to non-ionic SmA phases.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…[12][13][14][15][16] We have previously identied ILCs 1, 2 showing rare SmC phases (Scheme 1), which consist of a calamitic core unit carrying one side chain and a exible spacer connected to a cationic head group. [15][16][17][18] Upon examination of the order parameter of the SmA phase of these compounds it was found that the long range orientational order (S 2 ) in the SmA phase was much smaller as compared to the values obtained for SmA phases from non-ionic liquid crystals. [19][20][21][22] On the other hand, the 1D translational order (smectic order parameter 3) of the SmA phase of ILCs is much larger 17,18 as compared to non-ionic SmA phases.…”
Section: Introductionmentioning
confidence: 82%
“…[15][16][17][18] Upon examination of the order parameter of the SmA phase of these compounds it was found that the long range orientational order (S 2 ) in the SmA phase was much smaller as compared to the values obtained for SmA phases from non-ionic liquid crystals. [19][20][21][22] On the other hand, the 1D translational order (smectic order parameter 3) of the SmA phase of ILCs is much larger 17,18 as compared to non-ionic SmA phases. [23][24][25][26] Thus ILCs possess a high lamellar order but only a low long range orientational order as compared to neutral liquid crystals and in that respect behave similar to the so called de Vries materials.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…[43] Indeed, guanidinium ions are known building blocks that support mesomorphism of ionic liquid crystals (ILCs). [44][45][46][47] ILCs are anisotropic fluids with long-range orientational order caused by Coulombic interactions between cationic headgroups and counterions,nanosegregation between immiscible parts (that is,a ni onic headgroup,r igid core,a nd lipophilic tail), minimization of free volume complemented by van der Waals interactions, p-p,a nd hydrogen bonding interactions. [44,45] As ILCs have been reported to serve as al ink between neutral liquid crystals and polyelectrolytes, [48] insight into the structure-property relationships of aminocyclopropenium-derived ILCs should enable better tuning of the corresponding polyelectrolytes carrying aminocyclopropenium units for both batteries and fuel cells, [27][28][29][30][31][32]49,50] as well as gene-delivery vectors [51,52] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%